Physical activity and advanced cancer: evidence of exercise‐sensitive genes regulating prostate cancer cell proliferation and apoptosis. (28th July 2020) - Schwappacher, Raphaela; Schink, Kristin; Sologub, Svetlana; Dieterich, Walburga; Reljic, Dejan; Friedrich, Oliver; Herrmann, Hans J.; Neurath, Markus F.; Zopf, Yurdagül
Abstract : Key points: Physical activity is known to protect against cancer. The resistance exercise method whole‐body electromyostimulation (WB‐EMS) has a significant anti‐cancer effect. WB‐EMS‐conditioned serum from advanced prostate cancer patients decreased human prostate carcinoma cell growth and viability in vitro . Multiplex analysis revealed that genes associated with human prostate cancer cell proliferation and apoptosis are sensitive for exercise. Feasible exercise should be part of multimodal anti‐cancer therapies, also for physically weakened patients. Abstract: Regular physical activity is known to protect against cancer development. In cancer survivors, exercise reduces the risk of cancer recurrence and mortality. However, the link between exercise and decreased cancer risk and improved survival is still not well understood. Serum from exercising healthy individuals inhibits proliferation and activates apoptosis in various cancer cells, suggesting that mechanisms regulating cancer cell growth are affected by exercise. For the first time, we analysed serum from advanced‐stage cancer patients with prostate (exercise group n = 8; control group n = 10) or colorectal (exercise n = 6; control n = 6) cancer, after a 12‐week whole‐body electromyostimulation training (20 min/session, 2×/week; frequency 85 Hz; pulse width 350 µs; 6 s stimulation, 4 s rest), a tolerable, yet effective, resistance exercise for physically weakened patients. We report that serum from these advanced cancer patients inhibits proliferation and enhances apoptosis of human prostate and colon cancer cells in vitro using cell growth and death assays (5‐bromo‐2′‐deoxyuridine incorporation, cell counting, DNA fragmentation). Exercise‐mimicking electric pulse stimulation of human primary myotubes showed that electric pulse stimulation‐conditioned myotube medium also impairs human cancer cell viability. Gene expression analysis using a multiplex array of cancer‐associated genes and subsequent quantitative RT‐PCR revealed the presence of exercise‐sensitive genes in human prostate cancer cells that potentially participate in the exercise‐mediated regulation of malignant cell growth and apoptosis. Our data document the strong efficiency of the anti‐oncogenic effects of physical activity and will further support the application of regular therapeutic exercise during cancer disease. Key points: Physical activity is known to protect against cancer. The resistance exercise method whole‐body electromyostimulation (WB‐EMS) has a significant anti‐cancer effect. WB‐EMS‐conditioned serum from advanced prostate cancer patients decreased human prostate carcinoma cell growth and viability in vitro . Multiplex analysis revealed that genes associated with human prostate cancer cell proliferation and apoptosis are sensitive for exercise. Feasible exercise should be part of multimodal anti‐cancer therapies, also for physically weakened patients.